THE INFLUENCE OF THE WORK "SHAKHNAMA" ON SOCIO-CULTURAL AND POLITICAL PROCESSES IN THE MUSLIM EAST (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the history of the creation, content, and ideological and spiritual significance of the great Persian-Tajik poet Abulqasim Firdausi and his rare work, the "Shahnama". The Samanid era, in which the poet lived, was a period of high science, literature, and religious tolerance, and this environment had a strong influence on the creative formation of Firdausi. The work "Shahnama" glorifies such ideas as the history of the peoples of Iran and Turan, national identity, justice, and love for the Motherland. The article also examines the conflict between Firdausi and Sultan Mahmud, and the views of Eastern and Western researchers who assessed the historical and cultural role of the "Shahnama". The work is analyzed as an epic epic that occupies a special place in the Uzbek and world literary heritage.